2009
DOI: 10.1111/j.1365-2893.2009.01080.x
|View full text |Cite
|
Sign up to set email alerts
|

Low uptake of treatment for hepatitis C virus infection in a large community‐based study of inner city residents

Abstract: Despite the availability of effective therapy for hepatitis C virus (HCV) infection, there are little data on the uptake of treatment. We evaluated factors associated with HCV infection and the uptake of HCV treatment in a large community-based inner city cohort in Vancouver, Canada. The Community Health and Safety Evaluation is a cohort study of inner city residents recruited from January 2003 to June 2004. HIV and HCV status and information on prescriptions for HCV treatment were determined through linkage w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
131
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(152 citation statements)
references
References 28 publications
17
131
1
3
Order By: Relevance
“…[16], and in a German and Swedish HIV/HCV cohort treatment rates were 40% and 25%, respectively [17,18]. In a large US cohort of veterans only 12% of monoinfected patients received therapy between 2000 and 2005 [19]; in coinfected populations treatment uptake was even lower [20,21]. Predictors for treatment uptake, including genotype 3, MSM, younger age, no psychiatric disorders and controlled HIV-infection, indicate that therapy was started in the easier-to-treat patients.…”
Section: Hcv Treatment Uptakementioning
confidence: 92%
“…[16], and in a German and Swedish HIV/HCV cohort treatment rates were 40% and 25%, respectively [17,18]. In a large US cohort of veterans only 12% of monoinfected patients received therapy between 2000 and 2005 [19]; in coinfected populations treatment uptake was even lower [20,21]. Predictors for treatment uptake, including genotype 3, MSM, younger age, no psychiatric disorders and controlled HIV-infection, indicate that therapy was started in the easier-to-treat patients.…”
Section: Hcv Treatment Uptakementioning
confidence: 92%
“…Further it is reported that primary care physicians rarely refer HCV patients for subspecialty assessment and only one-half of HCV infected patients are referred to a specialist for evaluation and management [95]. Boaz and colleagues [96] told that referral of HCV patients with normal liver tests is below 30%. Moreover, for those patients referred for treatment, the accessibility to specialists act as an additional hurdle.…”
Section: Provider Factorsmentioning
confidence: 99%
“…taux de traitement oscillant entre 1 et 6 %, alors que plus de 70 % en font la demande (Grebely, 2009 ;Sherman, 2007). De plus, les personnes avec des troubles mentaux sont souvent jugées admissibles au traitement (Freedman, 2009).…”
Section: Tableau 1 Effets Indésirables Associés Aux Traitements Pharmunclassified
“…Elle permet aussi de définir certaines conditions préalables au traitement et qui feront l'objet d'un premier plan d'intervention (la stabilisation d'une condition psychiatrique, l'augmentation du contrôle sur certains aspects de la consommation de substances ou l'obtention d'un domicile fixe, par exemple). L'adhésion à ces premiers rendez-vous est reconnue comme un bon indicateur du degré d'engagement du patient (Grebely, 2009) et permet de mettre en évidence les difficultés à envisager à cet égard lors d'un éventuel traitement.…”
Section: Développement Et Organisation Du Programme Actuel Au Chum Leunclassified
See 1 more Smart Citation